The Future of Imaging in Detecting Glaucoma Progression - Lavinsky, Fabio (Ophthalmology, 2017)
Ocular imaging has been heavily incorporated into glaucoma management and provides important information that aids in the detection of disease progression. Longitudinal studies have shown that the circumpapillary retinal nerve fiber layer is an important parameter for glaucoma progression detection, while other studies demonstrated that macular parameters, such as the ganglion cell inner plexiform layer and optic nerve head parameters are also useful for progression detection. The introduction of novel technologies with faster scan speeds, wider scanning fields, higher resolution, and improved tissue penetration has enabled the precise quantification of additional key ocular structures, such as the individual retinal layers, optic nerve head, choroid, and lamina cribrosa. Furthermore, extracting functional information from scans such as blood flow rate and oxygen consumption provides new perspectives on the disease and its progression. These novel methods promise improved detection of glaucoma progression and better insight into the mechanisms of progression that will lead to better targeted treatment options to prevent visual damage and blindness.